Unmute - Libot, Judiel Gwen M. (Animo Repository, 2022)
Unmute is a multiperspective crowdsourced short documentary about the online learning experience of college students in the Philippines. From the start of the pandemic to the announcement of face-to-face classes, Unmute follows the psychological turmoil college students faced brought about by social and economic factors. It features the experiences of various students from different backgrounds, and expertise from a registered psychologist. Furthermore, the documentary sheds light on the importance of strengthening the Philippines’ educational system and mental health response. By crowdsourcing footage from social media, the documentary was able to depict a multidimensional time capsule of online learning. After months of crowdsourcing content, 48 perspectives— including our own— were selected to retell the cumulative experience of most Filipino college students who underwent online learning. Although it was more desirable to capture everyone’s experience in the documentary, especially those in far-flung communities that have poor internet access, the pandemic restricted the scope of this project. Unmute is a hybrid production comprising of observational and directed shots made by the filmmakers and their collaborators (the subjects). In doing so, it enabled the project to explore different perspectives while providing clear context of the online learning experience of tertiary students. All forms of contact were made through social media while the interviews were done through the video conferencing platform Zoom. Additionally, all materials used were granted permission by the owner or are in use under the creative common license and/or fair use. Overall, the documentary aims to Libot & Olfato 6 destigmatize mental health and stress the need for educational system reform in the Philippines. 1080p MP4 format. 9:16 (vertical) aspect ratio.